A Fuzzy Analytic Hierarchy Process Approach for Determining the Criteria Success Factors of MRT Parts' e-Procurement: the Case of Jakarta MRT Project. (May 2019) - Hartanto, T; Ginting, M; Sunardi, O
Abstract: The Mass Rapid Transit (MRT) project is conducted by the central government in cooperation with the provincial government of DKI Jakarta and supported by the Japanese government through Japan International Cooperation Agency (JICA). The government goal is to create good e-Governance for the MRT project, and together initiate the use of e-Supply Chain Management (e-SCM), especially the e-Procurement, for the entire project. Technological innovation which is collaborated within the e-SCM becomes a very important aspect to support the e-Governance. This paper aims to determine the criteria and sub-criteria of success of the implementation of MRT parts' e-Procurement, and to determine the priorities of the MRT parts' e-Procurement process for the provincial government of DKI Jakarta. Fuzzy Analytic Hierarchy Process was employed to explore and simulate the level of importance of criteria and sub-criteria, in relations with the successful implementation of e-Procurement in MRT project. Top management commitment was found to be the most influential criteria by 0.334, followed by government policy and regulation (0.305), technology infrastructure (0.176), value acquisition (0.103), and suppliers' relations (0.082).